Capturing Public Opinion on Public Health Topics: A Comparison of Experiences from a Systematic Review, Focus Group Study, and Analysis of Online, User-Generated Content - Giles, Emma Louise; Adams, Jean M. (Frontiers in Public Health, 2015)
Background Capturing public opinion towards public health topics is important to ensure that services, policy and research are aligned with the beliefs and priorities of the general public. A number of approaches can be used to capture public opinion. Methods We are conducting a programme of work on the effectiveness and acceptability of health promoting financial incentive interventions. We have captured public opinion on financial incentive interventions using three methods: a systematic review, focus group study, and analysis of online user-generated comments to news media reports. In this short, editorial-style, piece we compare and contrast our experiences with these three methods. Results Each of these methods had their advantages and disadvantages. Advantages include tailoring of the research question for systematic reviews, probing of answers during focus groups, and the ability to aggregate a large data set using online user-generated content. However, disadvantages include needing to update systematic reviews, participants conforming to a dominant perspective in focus groups, and being unable to collect respondent characteristics during analysis of user-generated online content. That said, analysis of user-generated online content offers additional time and resource advantages, and we found it elicited similar findings to those obtained via more traditional methods, such as systematic reviews and focus groups. Conclusions A number of methods for capturing public opinions on public health topics are available. Public health researchers, policy makers and practitioners should choose methods appropriate to their aims. Analysis user-generated online content, especially in the context of news media reports, may be a quicker and cheaper alternative to more traditional methods, without compromising on the breadth of opinions captured.